We are the Greeks and our Uncertainty. Sociological Approach to the Ancient Greek World - Roche Cárcel, Juan Antonio (Política y Sociedad, 2016)
The aim of this article is to make a sociological approach to the issues that have occupied the most important sociologists in her gaze to Greek universe. To do this, we will establish a link between debates and concerns of Sociological Theory and the reflections of many Hellenists in order to make an inventory of this thematic. Likewise, we`ll intend to find the Greek origin of concepts like human beings, society, city or contemporary democracy in order to obtain alternatives to some of our most pressing social problems from Hellenic knowledge.